Sphingosine-1-Phosphate and the S1P3 Receptor Initiate Neuronal Retraction via RhoA/ROCK Associated with CRMP2 Phosphorylation - Quarta, Serena; Camprubí-Robles, Maria; Schweigreiter, Rüdiger; Matusica, Dusan; Haberberger, Rainer V.; Proia, Richard L.; Bandtlow, Christine E.; Ferrer-Montiel, Antonio; Kress, Michaela (Frontiers in Molecular Neuroscience, 2017)
The bioactive lipid sphingosine-1-phosphate (S1P) is an important regulator in the nervous system. Here, we explored the role of S1P and its receptors in vitro and in preclinical models of peripheral nerve regeneration. Adult sensory neurons and motor neuron-like cells were exposed to S1P in an in vitro assay, and virtually all neurons responded with a rapid retraction of neurites and growth cone collapse which were associated with RhoA and ROCK activation. The S1P1 receptor agonist SEW2871 neither activated RhoA or neurite retraction, nor was S1P-induced neurite retraction mitigated in S1P1-deficient neurons. Depletion of S1P3 receptors however resulted in a dramatic inhibition of S1P-induced neurite retraction and was on the contrary associated with a significant elongation of neuronal processes in response to S1P. Opposing responses to S1P could be observed in the same neuron population, where S1P could activate S1P1 receptors to stimulate elongation or S1P3 receptors and retraction. S1P was, for the first time in sensory neurons, linked to the phosphorylation of collapsin response-mediated protein-2 (CRMP2), which was inhibited by ROCK inhibition. The improved sensory recovery after crush injury further supported the relevance of a critical role for S1P and receptors in fine-tuning axonal outgrowth in peripheral neurons.